PENGARUH STRUKTUR VEGETASI TERHADAP KELIMPAHAN KERANG KEPAH (Polymesoda erosa) PADA HUTAN MANGROVE DESA SUNGAI BAKAU KECIL KABUPATEN MEMPAWAH KALIMANTAN BARAT - Sutardi, Aldi; Anwari, Sofwan; Rifanjani, Slamet (JURNAL HUTAN LESTARI, 2018)
Mangrove forests are one of the ecosystems that have important values in terms of physical, biological and economic. Increasing the quality of forests can increase the usefull of one of the biological benefits. This can be seen by many animals that use the forest as a shelter, spawning, foraging and so forth. One of the mangrove forest in Sungai Bakau Kecil`s Village, Mempawah, West Kalimantan. The purpose of this study was to determine the effect of density and vegetation structure on the abundance of shellfish.The method used in this research was survey. Determination of starting point as the first line of observation was done purposively (placement deliberately), for the next path systematically with a distance of 100 m. Observation of mangrove vegetation was pathway technique. Each path was made of 3 plots of observation of mangrove vegetation and shellfish with each plot area of 10 m X 10 m. The plot was made perpendicular to the coastline, the first plot was near the beach then the second plot was made 50 m from the first plot and the third plot was made 50 m from the second plot. The samples was made of 3 quadran with 1m x 1m for shellfish samples .The highest density of vegetation with the highest shellfish was found in observation plots 3, 6 and 9 with each density of Vegetation in plot 3, 6, 9 were 7851/Ha, 13029/Ha and 5261/Ha respectively, and the range of 6-8 shellsfish. Vegetation structure at 3, 6 and 9 observation plots that can provide food, space and temperature that support for shellfish with tree density of 9-17/Ha, stakes 256-512/Ha and seedlings 5000-12500/Ha.Keywords: Mangrove, Shellfish, Vegetation